2020
DOI: 10.3389/fendo.2020.594264
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Response With the Combination of Nivolumab and Cabozantinib in a Patient With Metastatic Paraganglioma: A Case Report and Review of the Current Literature

Abstract: IntroductionPheochromocytomas and sympathetic paragangliomas (PPGL) are neuroendocrine catecholamine-secreting tumors that are usually localized. Metastatic disease is rare and systemic treatment consists of conventional chemotherapy and high-specific-activity iodine-131-MIBG which was approved by the FDA in 2018. Although chemotherapy combinations still have value in specific settings, the debilitating side effects of treatment with only modest benefit have limited their use. With the introduction of a new ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Combining cabozantinib with nivolumab was associated with a PR, disease stabilization, the disappearance of the symptoms of catecholamine excess, and an acceptable toxicity, and the clinical benefits of this combined therapy lasted for 22 months. This case report suggests that cabozantinib could have induced some degree of tumor vascular normalization that facilitated the activation of the immune system [73].…”
Section: Does Immunotherapy With Checkpoint Inhibitors Work For Mppgl?mentioning
confidence: 78%
“…Combining cabozantinib with nivolumab was associated with a PR, disease stabilization, the disappearance of the symptoms of catecholamine excess, and an acceptable toxicity, and the clinical benefits of this combined therapy lasted for 22 months. This case report suggests that cabozantinib could have induced some degree of tumor vascular normalization that facilitated the activation of the immune system [73].…”
Section: Does Immunotherapy With Checkpoint Inhibitors Work For Mppgl?mentioning
confidence: 78%
“…Recently developed ICI may offer new therapeutic opportunities for this disease. In fact, a first clinical trial revealed that some patients with metastatic PPGL gained a moderated but, in some cases, durable clinical benefit when treated with pembrolizumab [ 16 , 37 ]. Knowledge of CTL tumor infiltration and PD‐L1 expression levels in PPGL are the basis for ICI‐based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the literature, there is a case report of a 32-year-old male patient suffering from an advanced metastatic paraganglioma, showing a progressive disease when enrolled in a CBZ-based trial as a monotherapy treatment. Nonetheless, he showed prolonged disease control with a significant tumour reduction and decrease in metastatic burden when enrolled in the study by Apolo (started on CBZ plus nivolumab) [ 61 , 62 ]. A phase II clinical trial on CBZ in monotherapy is now recruiting patients with unresectable metastatic paraganglioma or pheochromocytoma (Table 3 - https://clinicaltrials.gov ).…”
Section: Thyroid Cancersmentioning
confidence: 99%